FRI0135 Unexpected High Prevalence of Cardiac Disease in Patients with Ankylosing Spondylitis. (10th June 2014) - Heslinga, S.C.; Konings, T.C.; Van der Horst-Bruinsma, I.E.; John, M.; Nurmohamed, M.T.
Abstract : Background: Ankylosing spondylitis (AS) is associated with an increased cardiovascular (CV) risk that is caused by accelerated atherosclerosis as well as specific cardiac manifestations: valvular disease, conduction disturbances and congestive heart failure due to decreased ventricular function. Objectives: In this study we investigated the prevalence of cardiac disease in AS patients with high disease activity. Methods: We performed a cross sectional study in patients with AS eligible for treatment with TNF blocking therapy. Patients were screened for cardiac disease using standard transthoracic echocardiography that included two-dimensional, three-dimensional and M-mode echocardiography, spectral Doppler, color Doppler and tissue Doppler imaging. Ejection fraction (EF) was used to assess systolic left ventricular (LV) function, with systolic LV dysfunction defined as EF<50%. For diastolic LV function a combination of echocardiographic measurements, i.e. peak early diastolic filling velocity (E), late diastolic filling velocity (A), E/A ratio, deceleration time (DT) and isovolumetric relaxation time (IVRT) were used. Based on these parameters diastolic LV dysfunction is graded into three categories: mild (grade I), pseudonormal (grade II) and restrictive (grade III). Valvular abnormalities were evaluated according to current echocardiographic guidelines. Data was compared with data from literature using one-sample t-test. Results: Thirty-six consecutive AS patients were included with a mean age of 44±12 years and a mean disease duration of 10±12 years. In total, 8 out of 36 (22%) patients had diastolic LV dysfunction grade I, of which one was female. This was significantly higher compared to literature, in which the prevalence of diastolic LV dysfunction grade I is approximately 5% in an age matched control group (p<0.01) 1 . Two patients had a prior myocardial infarction of which one had systolic LV dysfunction, with an EF of 49%. Two patients had mild aortic regurgitation, seven other patients had mild mitral regurgitation, and one had both. Overall, 14 out of 36 (39%) patients had some form of cardiac disease which is substantially higher compared to the general population, as the prevalence of cardiac disease in the general population is approximately 8% 2 . Conclusions: Patients with AS have a more than fourfold increased prevalence of cardiac disease compared with the general population, with high prevalences of diastolic LV dysfunction and valvular disease. This increased prevalence may increase CV risk in AS patients. As cardiac disease could be attributable to the general inflammation process affecting the heart, further studies are warranted that investigate whether or not anti-inflammatory treatment, such as TNF blockers, improves cardiac function or prevents early cardiac complications. Also, the impact of (mandatory) screening AS patients with echocardiography on CV disease should be investigated. References: Redfield et al 2003, The burden of systolic and diastolic ventricular dysfunction in the community Lindekleiv et al 2013, Echocardiographic screening of the general population and long term survival Disclosure of Interest: S. Heslinga: None declared, T. Konings: None declared, I. Van der Horst-Bruinsma Grant/research support: This is an investigator initiated study financed by an unrestricted grant from MSD, The Netherlands, M. John: None declared, M. Nurmohamed Grant/research support: This is an investigator initiated study financed by an unrestricted grant from MSD, The Netherlands DOI: 10.1136/annrheumdis-2014-eular.3498